ANALISIS STRUKTUR MODAL PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuwono, Wisnu; Momongan, Mixci Daniel Momongan; Sanjaya, Kelvin; Susiana, Fendrawati; Duchovny Young, Hepi (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This study aims to design a model framework of variables that determinants of capital structure. Board size, CEO duality, board composition, managerial ownership and CEO tenure were determined as independent variables that affect capital structure. Profitability and firm size were used as control variables. The meta analysis is the method used in the preparation of articles. The secondary data obtained is the result of research from previous researchers. The preparation of this study produces a model framework that can be used as a guide in formulating strategies as well as a consideration tool in making effective and efficient capital structure decisions so as to maximize company value and prevent bankruptcy.